Basic Teaching Skills for Teachers at SD GP Kumelembuai - Romi Mesra; Afriono Tagaku; Triven Simbar; Seltia Wangkanusa; Siska Mangar; Olvinia A. C Podung; Anjelita Andale (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses a study that takes a closer look at how educators carry out the teaching and learning process using curriculum development and basic education evaluation systems that have been implemented properly. Basic teaching skills are important for teachers to know and implement. It is related to the effectiveness of the teacher in the teaching and learning process carried out in learning. The purpose of the research is to describe how basic teacher-teaching skills are implemented at SD GP Kumelembaai. The research is a descriptive qualitative research. The research data and findings come from the value of skills that form the basic education of grade 1, 2, and 3 teachers at SD GP Kumelembai. The data collected are data about the basic teaching skills of teachers through the stages of observation, interviews, and documentation. Based on the research findings and basic teaching skills, teachers in remote areas, especially at SD GP Kumelembai, are not yet skilled in applying basic teaching skills in learning, such as opening and closing lessons, asking questions, explaining, guiding small group discussions, teaching individually, managing classes, providing reinforcement, and providing variety.